2006
DOI: 10.1111/j.1365-2249.2006.03115.x
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmunity to type VII collagen in SKH1 mice is independent of regulatory T cells

Abstract: SummaryEpidermolysis bullosa acquisita is an autoimmune blistering disease characterized by circulating and skin basement membrane-bound IgG autoantibodies to type VII collagen, a major structural protein of the dermal-epidermal junction. Regulatory T cells (T reg ) suppress self antigen-mediated autoimmune responses. To investigate the role of T reg in the the autoimmune response to type VII collagen in a mouse model, a monoclonal antibody against mouse CD25 was used to deplete T reg . A recombinant mouse typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…Meanwhile, Chen et al . have reported that the depletion of Tregs by anti‐mouse CD25 antibody did not affect the production of anti‐COL7 antibody in SKH1 mice immunized with mouse COL7, suggesting that the development of autoimmunity against COL7 in mice is independent of Treg function. Hence, the role of Tregs in the induction and/or the progression of AIBDs should be further investigated.…”
Section: Potential Therapeutic Strategies For Targeting Autoreactive mentioning
confidence: 99%
“…Meanwhile, Chen et al . have reported that the depletion of Tregs by anti‐mouse CD25 antibody did not affect the production of anti‐COL7 antibody in SKH1 mice immunized with mouse COL7, suggesting that the development of autoimmunity against COL7 in mice is independent of Treg function. Hence, the role of Tregs in the induction and/or the progression of AIBDs should be further investigated.…”
Section: Potential Therapeutic Strategies For Targeting Autoreactive mentioning
confidence: 99%
“…The addition of other adjuvants like CpG, pertussis or cholera toxins increases the efficacy of the immunization and results in SJL‐1 mice in a stronger autoimmune response and a more extensive blistering skin disease (Sesarman A and Sitaru C, unpublished). Various inbred and outbred mouse strains, including BALB/c, C57BL/6, SJL‐1, AJ and SKH‐1, are prone to develop an autoimmune response upon immunization with murine type VII collagen (56,70). However, the genetic background appears to strongly influence the development of the blistering disease in these mice.…”
Section: The Active Disease Model Of Ebamentioning
confidence: 99%
“…Thus, SJL‐1 mice qualify as high responders with an incidence of 80–100%, whereas only about 50% of the immunized BALB/c mice develop a significantly milder disease (56). In contrast, other strains, including C57BL/6 and the outbred SKH‐1 mice, are completely resistant to the induction of experimental EBA by immunization (56,70). All mice developed circulating IgG autoantibodies that recognized type VII collagen and bound to the lamina densa of the dermal–epidermal junction.…”
Section: The Active Disease Model Of Ebamentioning
confidence: 99%
“…However, the role of Treg cells in EBM remains unclear. Depletion of the Treg cells with an antibody did not affect the autoimmune response type VII collagen in a mouse model (11). This mouse model reproduced auto-antibody production against type VII collagen, but not blistering ( 12).…”
Section: Discussionmentioning
confidence: 94%